Technology Utilization in Physical Education Learning in Elementary Schools: A Systematic Literature Review - Putri, Septia Zalika; Yopi Hutomo Bhakti (Universitas Pendidikan Ganesha, 2025)
Physical education learning in primary schools faces challenges in improving student motivation, effectiveness and engagement. The utilization of technology is one of the innovative solutions to improve the quality of learning in this area. This study used the Systematic Literature Review (SLR) method to analyze the effectiveness of technology in physical education learning in primary schools. Eight articles from the Scopus database published between 2019 and 2023 were systematically analyzed. The results showed that technology, such as sports apps, wearables, exergames and virtual reality, can improve students' motivation, learning outcomes and engagement. However, the effectiveness of technology depends on the type of material, where material that requires direct physical activity is more effective using traditional methods. Data were collected through literature analysis with strict inclusion and exclusion criteria, then analyzed using a thematic synthesis approach. This research has implications for the need for learning strategies that optimally integrate technology to align with physical education objectives. Thus, teachers and policy makers are expected to adapt technological innovations to improve the effectiveness of physical education learning in primary schools.